2008
DOI: 10.1097/ta.0b013e31818c262f
|View full text |Cite
|
Sign up to set email alerts
|

Let the Surgeon Sleep: Trauma Team Activation for Severe Hypotension

Abstract: Changing criteria for TTA from SBP 90 mm Hg to <80 mm Hg preserves personnel without patient harm. Lowering the SBP for TTA is one method of preserving trauma surgery manpower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…However, such broad inclusion criteria would have significant implications for the delivery of care and possible overtriage, 46 given the limited resources available for trauma care. Currently, there is much debate in the emergency and trauma community about inappropriate trauma “activations” (which alert the hospital to the need for trauma resources such as the surgical and anesthesia team) from the field during the prehospital phase, 4749 or while in hospital, 50 and unnecessary transfers that deplete the hospital of needed resources and other patients. 51 In fact, studies of centers that do have age as a criterion for automatic trauma activation demonstrate that such regulation can result in unnecessary and costly initiations of a multidisciplinary response.…”
Section: Commentmentioning
confidence: 99%
“…However, such broad inclusion criteria would have significant implications for the delivery of care and possible overtriage, 46 given the limited resources available for trauma care. Currently, there is much debate in the emergency and trauma community about inappropriate trauma “activations” (which alert the hospital to the need for trauma resources such as the surgical and anesthesia team) from the field during the prehospital phase, 4749 or while in hospital, 50 and unnecessary transfers that deplete the hospital of needed resources and other patients. 51 In fact, studies of centers that do have age as a criterion for automatic trauma activation demonstrate that such regulation can result in unnecessary and costly initiations of a multidisciplinary response.…”
Section: Commentmentioning
confidence: 99%
“…Lehman et al, 21,22 reassessing triage criteria for trauma team activation at their center, deemed SBP of Ͻ100 mm Hg along with other variables as better criterion. However, Shapiro et al 23 found no harm in choosing a SBP of Ͻ80 mm Hg as definition of hypotension for trauma team activation at their trauma center when using resource allocation as the key variable.…”
mentioning
confidence: 98%
“…The majority of the data currently used to design triage systems comes from experiences at Level 1 centers, and may not take into account the significant differences in resources and infrastructure at Level 2 or 3 centers. 7 Our Level 2 trauma center had previously used the Pierce Country emergency medical system (EMS) Trauma Triage System (Fig. 1), a 3-tiered graded system of trauma activation that considered physiologic, demographic, and mechanistic variables to determine the level of trauma team activation.…”
mentioning
confidence: 99%